Empowerment of rural Youth through sericulture in andhra Pradesh - present scenario and prospects ahead - Smitha, S; Seshagiri, SV; Goel, AK; Raju, PJ (Journal of Agricultural Extension Management, 2018)
The youth are considered as the backbone and cream of the nation. Youth are the primary productive human resource of socio-economic development. It is therefore, essential to locate the role of youth in mainstream development. Youth are the important asset of a nation but they are being exploited by different agencies and their capabilities and competencies are not fully utilized by the nation. Rural youth are not only the future of food security but also for the growth of agriculture and development of allied enterprises. Rural youth face many hurdles while trying to earn a livelihood. While most of the world’s food is produced by (ageing) smallholder farmers in developing countries, older farmers are less likely to adopt the new technologies needed for sustainable increase in agricultural productivity and ultimately feed the growing world population. The focus should be on how to make agriculture and allied enterprises such as Sericulture, Animal husbandry etc., more attractive and rewarding to the younger generation. Being a rural agro-based labour intensive industry, the sericulture sector plays a vital role for checking the migration from rural to urban areas. The very nature of this industry with its rural based on farm and off-farm activities and enormous employment generation potential attracted the attention of policy makers to recognize the industry as one of the most appropriate avenues for socio-economic development of a largely agrarian economy like India. Hence, we need to engage youth in agriculture and allied enterprises like sericulture.